Defining visual rhetorics - Hill, Charles A.; Helmers, Marguerite H., 1961- (Lawrence Erlbaum, 2004)
Studing the relationship of visual images to persuasion, this book analyzes a wide variety of visual modes of communication that demonstrate some of the variety among the many kinds of texts that could be considered instances of visual rhetoric.